Studies on noise pollution in cotton ginneries - Arude, V G; Paralikar, K M (Journal of Agricultural Engineering, 2004)
Cotton ginning systems contain numerous types of machinery-each of which is a source of noise and contribute to the overall noise level. Noise pollution in cotton ginneries has never received attention in the past in India. Noise levels of different machineries used in cotton ginning systems were studied. The likely effect of noise on workers’ health and the possible ways of reducing the noise levels were suggested. Noise levels for double roller gins were found to vary from 87.0 to 97.7 dBA under no load and from 85.9 to 97.7 dBA under load condition. Noise for double roller gins were found above permissible exposure limit of 85 dBA. Gearbox of the double roller gin was found to generate more noise than other moving elements of the gin. Noise levels of pre-cleaners and lint cleaners were found below the permissible limit. In press house noise level was observed in the range of 793 to 93.5 dBA for different models of presses. Gin house was found to be the noisiest workstation with an average noise level of 96.0 dBA. The noise level for the workstations such as raw cotton suction fan, pre-cleaner, gin house, central platform, seed blower and press operator room were observed above the permissible exposure limit Exposure to such a noise may adversely affect overall efficiency, safety, and hearing ability of workers. Protecting them from loud noise by employing technical and personal measures of noise control can create healthful working conditions in ginneries.